The unity of the capitalist economy and state A systematic-dialectical exposition of the capitalist system - Reuten, Geert (Historical Materialism Book Series, 2019)
Geert Reuten's The unity of the capitalist economy and state offers a systematic exposition of the capitalist system. Outlining the economic and state institutions and processes that sustain capitalism, Reuten shows how the capitalist economy and state inevitably constitute a unity. Readership: Scholars and advanced students in political economy, economics, political science, social geography, sociology, and the philosophy of these sciences, and readers interested in a synthetic exposition of the capitalist system.